2015
DOI: 10.1002/bit.25708
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characteristics of virgin and fouled Protein A MabSelect resin cycled in a monoclonal antibody purification process

Abstract: The structural and functional characteristics of the Protein A MabSelect resin are determined for a virgin sample and for samples removed from a column that had been operated in an antibody capture process which had shown losses in product recovery over fewer than 20 cycles. Compared to the virgin resin, the cycled samples show reduced porosity and apparent pore size based on inverse size exclusion chromatography while transmission electron microscopy (TEM) shows accumulation of foulants on the cycled resin. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…TEM was performed after dehydrating the resin samples and washing them with increasing ethanol concentrations from 0 to 100% anhydrous ethanol. Sample was then embedded in LR-White resin and ultramicrotomed into sections and was viewed unstained11. It is observed that the fouled resin sample from the 100 th cycle exhibits deposition of foulants with a film thickness of 0.3 μm (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TEM was performed after dehydrating the resin samples and washing them with increasing ethanol concentrations from 0 to 100% anhydrous ethanol. Sample was then embedded in LR-White resin and ultramicrotomed into sections and was viewed unstained11. It is observed that the fouled resin sample from the 100 th cycle exhibits deposition of foulants with a film thickness of 0.3 μm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Each sample was then embedded in LR-White resin and ultramicrotomed into sections. For better contrast, sections of the virgin resin samples were stained with a mixture of uranyl acetate and lead citrate, while sections of the cycled samples were viewed unstained11.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have been carried out to confirm that mAb-HCP interactions were responsible for their lack of removal during protein A capture and subsequent polishing steps (Chollangi et al, 2015;Doneanu et al, 2012;Soderquist, Trumbo, Hart, Zhang, & Flynn, 2015;B. Zhang, Goetze, et al, 2016;S. Zhang, Goetze, et al, 2016;S.…”
Section: Introductionmentioning
confidence: 99%
“…CHT samples for TEM were prepared by immersing the particles in the acrylic resin LRWhite (London Resin Company, London, UK) and incubating them at 45°C overnight as discussed in reference [33][34] . The solid samples were then sectioned into 80 nm sections by ultramicrotome and viewed with a JEOL JEM-1230 transmission electron microscope.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%